Susceptibilidade a antibacterianos em bactérias da bacia hidrográfica do rio Toledo-PR. - Zine, Cristiane (2019)
Bacterial resistance is a major issue today, as certain antibiotics are losing their effectiveness to certain microorganisms. Given this, it is necessary to understand the action or not of heavy metals against antimicrobials, because "the constant presence of metals in the environment as a pollutant causes microorganisms to develop mechanisms of resistance to these compounds", because the metal may interfere with antimicrobial resistance depending the type of material the river may be receiving and its natural conditions. Thus, the objective of the present study was to identify if there is any correlation between the concentration of metals and the emergence of antimicrobial resistance. The study was carried out from September 2018 to February 2019. Ten points were studied, divided into two sections, rural and urban. For microbiological analysis, the multiple tube technique was used to determine the Most Probable Number. For antimicrobial resistance analyzes, antibiotics were dosed, filtered, separated into sterile vials and stored in a refrigerator until the time of use. In the physicochemical analyzes the Biochemical Oxygen Demand (BOD), and the metals were performed according to APHA, (2005). It was observed that the Ni and Cu concentrations are practically constant along the river. On the other hand, Pb and Fe concentrations showed significant differences along the entire river course. Metal concentrations, even above the limit values established by CONAMA Ordinance 357/2005, were not correlated with antibiotic efficiency, except for CU cation in relation to S + T antibiotic. The fecal and thermotolerant coliforms had a significant increase from the sampling point 6. There was an increase in BOD5 between points 6 and 9 and subsequent decline of this parameter. In this way, it can demonstrate that the river has a great capacity for self-purification and that in section 7 to 9 anthropogenic interference is responsible for the emergence of a potential source of reproductive resistance to at least one of the tested antibiotics (CEF).